The science of winning - Olbrecht, J. (F & G Partners, 2007)
The author has a Ph. D. in physiology and biomechanics from Cologne and is training adviser to numerous world class athletes - his method is based upon careful planning and a unique method of lactate testing to assess and optimize the athlete's conditioning and potential. J. O. has swum in three World Championships for Belgium. He is training adviser to several world class athletes (triathlon, swimming and others) and uses a unique method of lactate testing to assess the conditioning of his athletes. Jan believes in careful planning and in altitude training to optimize the athlete's conditioning and performance. He advises athletes whose races last from 20 seconds in swimming to over 8 hours in the Ironman.